Registration system for geotechnical logging and stereographic projection generation using Barton's Q index (LACCEI, 2024)
The geotechnical logging process of oriented boreholes is a crucial task in preventing rock slides and falls in mines. However, this process is tedious and requires the recording of a large amount of information, which can increase the risk of errors when using printed forms or spreadsheet. Additionally, the data processing carried out in the mining camp can require a lot of time and increase the risk of errors. This paper presents a software developed to optimize the geotechnical logging process of oriented boreholes. This software allows for immediate data processing and reduces the possibility of errors, contributing to the reduction of accidents in the mine. Furthermore, the software improves the recording and analysis process by 25% due to the decrease in time, improvements in data analysis, and increased accuracy in graph generation.